2013
DOI: 10.4187/respcare.01930
|View full text |Cite
|
Sign up to set email alerts
|

Maximum Rate of Pressure Development and Maximal Relaxation Rate of Respiratory Muscles in Patients with Cystic Fibrosis

Abstract: BACKGROUND: Respiratory muscle function in patients with cystic fibrosis (CF) has been studied by measurement of maximal inspiratory pressure (P Imax ), maximal expiratory pressure (P Emax ), and the pressure-time index of the respiratory muscles (PTI mus ). The maximum rate of pressure development (MRPD) during P Imax (MRPD-P Imax ), MRPD during P Emax (MRPD-P Emax ), maximal relaxation rate (MRR) during P Imax (MRR-P Imax ), and MRR during P Emax (MRR-P Emax ) have not been studied in CF. Our aim was to stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 28 publications
1
11
0
Order By: Relevance
“…Furthermore, in a more recent study including 5 hypercapnic patients recovering from acute respiratory failure, esophageal pressure swings, PTP and work of breathing (markers of respiratory effort) were significantly reduced with HFNT at 60 L/min [33]. This difference, however, may also stem from inherent differences in the structure and function of the diaphragm between COPD and CF patients [34]. …”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, in a more recent study including 5 hypercapnic patients recovering from acute respiratory failure, esophageal pressure swings, PTP and work of breathing (markers of respiratory effort) were significantly reduced with HFNT at 60 L/min [33]. This difference, however, may also stem from inherent differences in the structure and function of the diaphragm between COPD and CF patients [34]. …”
Section: Discussionmentioning
confidence: 99%
“…The findings imply that the expiratory muscles are well preserved. Dassios et al 9,18 likewise found that subjects with CF have adequate maximal expiratory pressures, CPF, and CPF/PEF ratios, and they suggested that the expiratory pressures needed for CPFs are preserved in patients with CF.…”
Section: Discussionmentioning
confidence: 98%
“…[5][6][7][8] The initial phase of cough is characterized by inhalation of gas that may be as little as 50% of the tidal volume or as great as 50% of the vital capacity (VC). 9 However, inhalation of a large volume of gas will produce greater lengthening of the expiratory muscles, which will generate greater positive intrathoracic pressures for a given expiratory phase. 9 The second phase of cough depends on expiratory muscle strength and adequate control of the upper airway to provide an explosive release of peak expiratory flow (PEF).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Direct measurements of respiratory muscle endurance via breathing against imposed external resistances would be a laborious task for patients with CF who are already using an appreciable fraction of their reserves to cope with everyday activity. Finally, portable equipment can be used to assess respiratory muscle function by measurement of the maximum relaxation rate (23), an index whose utility might be questionable due to the limited number of integer values that it attains in health and in CF. For these reasons, we suggest that measurement of τ, for the assessment of inspiratory muscle function in CF patients has considerable advantages.…”
Section: Inspiratory Muscle Relaxation In Cf Articlesmentioning
confidence: 99%